Transversus Abdominis Plane Catheter Bolus Analgesia after Major Abdominal Surgery - Nils Bjerregaard; Lone Nikolajsen; Thomas Fichtner Bendtsen; Bodil Steen Rasmussen (Anesthesiology Research and Practice)
Purpose. Transversus abdominis plane (TAP) blocks have been shown to reduce pain and opioid requirements after abdominal surgery. The aim of the present case series was to demonstrate the use of TAP catheter injections of bupivacaine after major abdominal surgery. Methods. Fifteen patients scheduled for open colonic resection surgery were included. After induction of anesthesia, bilateral TAP catheters were placed, and all patients received a bolus dose of 20 mL bupivacaine 2.5 mg/mL with epinephrine 5 μg/mL through each catheter. Additional bolus doses were injected bilaterally 12, 24, and 36 hrs after the first injections. Supplemental pain treatment consisted of paracetamol, ibuprofen, and gabapentin. Intravenous morphine was used as rescue analgesic. Postoperative pain was rated on a numeric rating scale (NRS, 0–10) at regular predefined intervals after surgery, and consumption of intravenous morphine was recorded. Results. The TAP catheters were placed without any technical difficulties. NRS scores were ≤3 at rest and ≤5 during cough at 4, 8, 12, 18, 24, and 36 hrs after surgery. Cumulative consumption of intravenous morphine was 28 (23–48) mg (median, IQR) within the first 48 postoperative hours. Conclusion. TAP catheter bolus injections can be used to prolong analgesia after major abdominal surgery.